Real bad Arabs how Hollywood vilifies a people - Shaheen, Jack, Dr.; Jhally, Sut; Earp, Jeremy; Media Education Foundation (Northampton, MA : Media Education Foundation, 2006)
Throughout its history Hollywood has portrayed Arabs as buffoons or bandits. The video seeks to rectify this sterotyping by comparing it to other forms of racist imagery and by suggesting alternative narratives that treat the Arabs as human, not demons
Introduction (3:20) -- Myths of Arabland (10:30) -- The Arab threat: mideast politics & Hollywood (4:36) -- Terror, Inc.: demonizing Palestinians & Muslims (7:40) -- The only good Arab (5:09) -- Islamophobia (6:19) -- Getting real (11:58)
Title from title screen
Based on the book of the same title by Jack Shaheen
Presenter: Jack Shaheen
In English with optional English or Arabic subtitles